Modeling polymeric gels : the role of chain flexibility on the structure of physical gels - Pereyra, Rodolfo Guillermo (2017)
Fil: Pereyra, Rodolfo Guillermo. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía, Física y Computación; Argentina.